A Resizing Method for 3D Visualization of Digital Elevation Models - Wei Yang; Kun Hou; Xintong Yu; Fanhua Yu (Institute of Advanced Engineering and Science, 2014)
The diversity and versatility of display devices today imposes new demands on digital elevation models (DEMs). This paper proposes a resizing method for 3D visualization of DEMs based on topographic feature. The proposed method improves seaming carving algorithm to resize DEMs instead of images according to the characterristics of DEMs. The proposed resizing method considers not only geometric constraints but also the characteristics of DEMs. Being different from the traditional reduction and expansion methods, the method not only resizes DEMs, but also preserves the characteristics of Digital Elevation Model. The method is implemented and experiments are carried out on actual DEM data. It can be seen from the comparison with scaling method that the proposed method is efficient and provides better 3D visualization of DEMs. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4044